Studies in Hinduism Historical Perspectives and Contemporary Developments - Sen, Amiya P. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This is a collection of articles by established scholars in the fields of History, Philosophy, Literature and Religious Studies. These are original essays which address the issues and concerns that now dominate the study of religion in its multiple dimensions with a fresh approach. They critique settled opinions and raise new and engaging questions concerning cultural hermeneutics and the academic study of religion. Embellished with a substantive and topical introduction by the editor, this collection of articles will be of abiding interest to scholars and interested lay persons alike.